2013
DOI: 10.1016/j.virusres.2012.09.011
|View full text |Cite
|
Sign up to set email alerts
|

NC-mediated nucleolar localization of retroviral gag proteins

Abstract: The assembly and release of retrovirus particles from the cell membrane is directed by the Gag polyprotein. The Gag protein of Rous sarcoma virus (RSV) traffics through the nucleus prior to plasma membrane localization. We previously reported that nuclear localization of RSV Gag is linked to efficient packaging of viral genomic RNA, however the intranuclear activities of RSV Gag are not well understood. To gain insight into the properties of the RSV Gag protein within the nucleus, we examined the subnuclear lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
80
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(83 citation statements)
references
References 91 publications
(120 reference statements)
3
80
0
Order By: Relevance
“…gBlock gene fragments (IDT, Coralville, IA) encoding RPS17 amino acids 21 to 76, with either K44/45A, K49A, K32/R33/K44/45/49A, or K32/R33/K49A changes, were inserted into the HEV P6 NheI/StuI infectious clone by using NheI and StuI restriction sites engineered at the 5= and 3= ends of the gBlock. Similarly, gBlocks encoding Rous sarcoma virus (RSV) nucleocapsid (NC) amino acids 15 to 73, RSV NC amino acids 15 to 73 with cysteines 21, 23, 47, and 50 and histidines 29 and 55 changed to glycine (36), yeast poly(A) binding protein amino acids 359 to 414 (37), and ribosomal protein L3 (RibL3; GenBank accession no. CAA51839.1) amino acids 18 to 73 were inserted into the HEV P6 NheI/StuI infectious clone by using NheI and StuI restriction sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…gBlock gene fragments (IDT, Coralville, IA) encoding RPS17 amino acids 21 to 76, with either K44/45A, K49A, K32/R33/K44/45/49A, or K32/R33/K49A changes, were inserted into the HEV P6 NheI/StuI infectious clone by using NheI and StuI restriction sites engineered at the 5= and 3= ends of the gBlock. Similarly, gBlocks encoding Rous sarcoma virus (RSV) nucleocapsid (NC) amino acids 15 to 73, RSV NC amino acids 15 to 73 with cysteines 21, 23, 47, and 50 and histidines 29 and 55 changed to glycine (36), yeast poly(A) binding protein amino acids 359 to 414 (37), and ribosomal protein L3 (RibL3; GenBank accession no. CAA51839.1) amino acids 18 to 73 were inserted into the HEV P6 NheI/StuI infectious clone by using NheI and StuI restriction sites.…”
Section: Methodsmentioning
confidence: 99%
“…In order to further evaluate which functional property of RPS17 contributes to the enhanced expression and in vitro host range expansion of the P6 HEV strain, we inserted amino acids 15 to 73 from the RSV NC protein. The NC region of RSV has a very wellclassified nuclear localization signal (36), and cysteine-histidine amino acid motifs are responsible for nucleic acid binding (43). Transfection of HEV RNA encoding either RSV NC or RSV NC with the cysteine-histidine box amino acids mutated to alanine (⌬Cys/His) into Huh7 cells resulted in the number of cells expressing the viral ORF2 protein resembling that for the HEV P1 strain.…”
Section: Rps17 and Rps19 Insertions Within The Hev Hvr Contain Nls Momentioning
confidence: 99%
“…We find this possibility to be quite intriguing because PI(4,5)P 2 is present in the nucleus and has been implicated in mRNA processing, mRNA export, chromatin remodeling, and transcriptional regulation (50-57), whereas nuclear PI(3,4,5)P 3 has been linked to the inhibition of apoptosis through its interaction with the nucleolar protein B23 (58). Thus, we propose the hypothesis that Gag may recruit nuclear PI(4,5)P 2 or PI(3,4,5)P 3 into the Gag-genomic RNA complex in the nucleus or nucleolus, as we have recently demonstrated nucleolar trafficking of RSV Gag (47). After exiting the nucleus through the nuclear pore, PI(4,5)P 2 or PI(3,4,5)P 3 may play a role in directing the viral ribonucleoprotein complex to the PM for final assembly of the virus particle.…”
mentioning
confidence: 69%
“…5A). We previously reported that these basic residues constitute an NLS in NC (21,46,47), so we examined whether the loss of the KKRK residues would reduce the nuclear localization of Gag.NC.M1 in the presence of a point mutation in p10 that disrupts the NES. Gag.L219A-YFP (Fig.…”
mentioning
confidence: 99%
“…This is supported by several pieces of evidence, including the presence of two nuclear localization signals in NC and MA recognized by different importins (21) and the detection of a large amount of RSV Gag in the nuclei of cells treated with leptomycin B (LMB) (22), a specific inhibitor of the karyopherin CRM1 (chromosome region maintenance 1 receptor) nuclear export pathway. An RSV Gag mutant that bypasses the nucleus packages vRNA less efficiently than the wild type (wt), and both nuclear trafficking and vRNA packaging is restored by the insertion of a heterologous nuclear localization signal (23,24). It has been suggested that the formation of the RSV Gag-vRNA complex induces a conformational change of Gag, which leads to the exposure of the nuclear export signal, a leucinerich region within p10 (25).…”
mentioning
confidence: 99%